How Buddhism Plays a Role through Victim-Offender Mediation in Handling the Challenges of Crime in China’s Tibet - Lu Feng (Religions, 2021)
Religion plays a significant role in the way Western societies respond to criminal offenses. However, the research on how religion plays a role in handling the challenges of crime in non-Western countries is lacking. In this study I try to close this research gap by analyzing the victim-offender mediation in China’s Tibet, where influenced by religion, history and culture, a set of local solutions to control criminal offenses have traditionally been formed. Based on the field survey and second-hand information, I discuss how religious factors play a role in local victim-offender mediation in terms of the basis for mediation, mediator, mediation tactics, and guarantee for mediation agreement. While Buddhism acts as a form of self-control over the adherents of Buddhism, it works as a form of social control as well. Buddhist lama as the main mediator strategically uses Buddhist principles as mediation tactics in victim-offender mediation. After the mediation agreement is reached, religious ceremony is usually conducted as a guarantee. In conclusion I summarize the possible contribution of the research findings to the basic issues of restorative justice.